ANALISIS IMPLEMENTASI APLIKASI SISTEM KEUANGAN DESA (SISKEUDES) TERHADAP KUALITAS LAPORAN KEUANGAN DI DESA PANGKAL BULUH - Ramadhan, Bram; Mulyani, Hendarti Tri Setyo; Medinal (Jurnal Akuntansi Bisnis Dan Keuangan, 2023)
The purpose of this research is to understand the extent to which the implementation of Siskeudes affects the quality of financial reports in Pangkal Buluh Village. The research method used is a qualitative approach using in-depth interviews and participatory observation as data collection techniques. Participants in this study were financial officers in Pangkal Buluh Village who used Siskeudes in their daily work. The results of this study indicate that the implementation of Siskeudes has a positive impact on the quality of financial reports in Pangkal Buluh Village. By using this application, the process of recording village financial transactions becomes more efficient and accurate. In addition, Siskeudes also allows for better oversight of village financial management, so that the potential for errors and fraud can be minimized.